Культурні румуно-сербські інтерференції в Банатському регіоні - Рістін., Д. (Народна творчість та етнологія, 2011)
This article is meant to reveal the different perspectives in which the Romanian and Serbian cultural interferences of Banat region could be noticed, pointing out their main common elements within a cross-cultural context. These facts are disscused taking into account the common background and all the conditions that made Banat region to become one of the most varied and interesting part of Europe, situated at the confluence of central and south-east European areas. There are relevant ethnographic, religious, folk, linguistic, and cultural characteristics within the framework of the cross-cultural communication between Romanian and Serbian people who live in Banat that can define a certain view of the world of both these two nations. Acest articol doreşte să evidenţieze perspectivele diferite din care pot fi privite interferenţele culturale dintre românii şi sârbii din regiunea Banatului, subliniind principalele elemente comune în cadrul unui context intercultural. Aceste fapte sunt discutate luând în considerare cadrul comun şi toate condiţionările care fac din regiunea Banatului una dintre cele mai variate şi mai interesante părţi ale Europei, situate la confluenţa dintre arealele central şi sud-est european. Caracteristici etnografice, religioase, folclorice, lingvistice şi culturale din cadrul comunicării intercultulturale dintre românii şi sârbii din Banat definesc o anumită viziune a universului celor două naţiuni.